Camellia suddeeana (Theaceae), a new species from Thailand - Zhao, Dongwei (Phytotaxa, 2023)
Camellia suddeeana, a new species endemic to northern Thailand that was previously misidentified as C. tenii, is described and illustrated here. It is similar to C. szemaoensis and C. hainingii for sharing the subsessile flower with white petals and distinct styles, but can be distinguished from the former by its glabrous abaxial surface of the sepals, ovary and seeds, leaves without cork-warts and a different flowering period, and from the latter by leaves without cork-warts and the longer styles. Based on its morphology, C. suddeeana may be placed in C. sect. Heterogena or C. sect. Furfuracea according to the classifications proposed by Ming and Chang, respectively.